2020
DOI: 10.1042/cs20200065
|View full text |Cite
|
Sign up to set email alerts
|

An inducible intestinal epithelial cell-specific NHE3 knockout mouse model mimicking congenital sodium diarrhea

Abstract: The sodium–hydrogen exchanger isoform 3 (NHE3, SLC9A3) is abundantly expressed in the gastrointestinal tract and is proposed to play essential roles in Na+ and fluid absorption as well as acid–base homeostasis. Mutations in the SLC9A3 gene can cause congenital sodium diarrhea (CSD). However, understanding the precise role of intestinal NHE3 has been severely hampered due to the lack of a suitable animal model. To navigate this problem and better understand the role of intestinal NHE3, we generated a tamoxifen-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 50 publications
5
39
0
Order By: Relevance
“…The deletion of NHE3 exacerbated experimental colitis in mice and developed IBD-like pathology [52][53][54][55]. Consistent with these findings, mice with intestinal epithelial-specific NHE3-deletion, displayed impaired barrier function and intestinal epithelial cell apoptosis that are characteristic of IBD [19]. Notably, the intestinal microbiome in NHE3 -/mice had lower microbial diversity and a change in the Firmicutes: Bacteroidetes ratio in favor of inflammation-associated Bacteroidetes, accompanied by a decline in butyrate-producing bacteria [52,54,72].…”
Section: The Ion-microbiome-immune Axis and Ibd Pathologysupporting
confidence: 65%
See 1 more Smart Citation
“…The deletion of NHE3 exacerbated experimental colitis in mice and developed IBD-like pathology [52][53][54][55]. Consistent with these findings, mice with intestinal epithelial-specific NHE3-deletion, displayed impaired barrier function and intestinal epithelial cell apoptosis that are characteristic of IBD [19]. Notably, the intestinal microbiome in NHE3 -/mice had lower microbial diversity and a change in the Firmicutes: Bacteroidetes ratio in favor of inflammation-associated Bacteroidetes, accompanied by a decline in butyrate-producing bacteria [52,54,72].…”
Section: The Ion-microbiome-immune Axis and Ibd Pathologysupporting
confidence: 65%
“…This finding brought a conceptual shift toward the importance of electrolyte homeostasis in IBD pathogenesis [18]. Recent years have seen significant progress in our understanding of the genetic heterogeneity of CSD and monogenic IBD, with mutations identified in additional genes that encode proteins that regulate intestinal sodium absorption, including SLC9A3, that encodes NHE3 [19], and SPINT2, that encodes a Kunitz-type serine protease inhibitor [4].…”
Section: Introductionmentioning
confidence: 99%
“…Laubitz et al, (2008) showed their age‐matched NHE3 KO mice were smaller than WT mice; however, their mice were on a different genetic background (black Swiss), exhibited only “mild” diarrhea and did not require fluid and electrolyte supplementation to enable survival past weaning. Recently, an inducible intestine‐only NHE3 KO was developed which led to a transient decrease in body mass followed by an increase relative to non‐induced controls with NHE3 KOs eventually becoming heavier than their WT age‐matched counterparts (Xue et al, 2020). From previous studies, the intestinal tract accounts for approximately 9–15% of the body mass in the adult NHE3 KO compared to 6–7% of total body mass in WT mice (Schultheis, Clarke, Meneton, Miller, et al, 1998; Xue et al, 2020), and likely explains why younger NHE3 KO mice in the current study had a similar body mass to their older WT counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an inducible intestine‐only NHE3 KO was developed which led to a transient decrease in body mass followed by an increase relative to non‐induced controls with NHE3 KOs eventually becoming heavier than their WT age‐matched counterparts (Xue et al, 2020). From previous studies, the intestinal tract accounts for approximately 9–15% of the body mass in the adult NHE3 KO compared to 6–7% of total body mass in WT mice (Schultheis, Clarke, Meneton, Miller, et al, 1998; Xue et al, 2020), and likely explains why younger NHE3 KO mice in the current study had a similar body mass to their older WT counterparts. This could have implications for interpretation of urinary oxalate and creatinine excretion rates as they are both closely linked to metabolic rate with the latter being tied to muscle mass (Perrone et al, 1992; Wyss & Kaddurah‐Daouk, 2000) which was visibly lower in the NHE3 KO cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma membrane-enriched samples (by centrifugation at 17,000 x g) were prepared for Western blotting. Proteins were transferred to polyvinylidene difluoride membranes and immunoblotted with AQP2 [36], pS256 AQP2 [41], V 2 R [42], AQP3 [43], NHE3 (AB3085, Millipore, Billerica MA; characterized in [44]), NKCC2 [37], NCC (SPC-402, StressMarq Biosciences, Cadboro Bay, Victoria, BC, Canada; characterized in [45]), H + -ATPase [46], αENaC (provided by Johannes Loffing, Institute of Anatomy, Zürich, Switzerland [47]), γENaC [48,49] and Na + /K + -ATPase (06-520, Merck Millipore, Darmstadt, Germany [48]). Chemiluminescent detection was performed with ECL Plus (Amersham, Piscataway, NJ).…”
Section: Immunoblot Analysismentioning
confidence: 99%